You are dead - James, Peter, 1948- (London: Macmillan, 2015)
"The last words Jamie Ball hears from his fiancée, Logan Somervile, are in a terrified mobile phone call from her. She has just driven into the underground car park beneath the apartment block where they live in Brighton, and seen a man acting strangely. Then she screams and the phone goes dead. The police are on the scene within minutes, but Logan has vanished, leaving behind her neatly parked car and cell phone. That same afternoon, workmen digging up an old asphalt path in a park in another part of the city, unearth the remains of a young woman in her early twenties, who has probably been dead for 30 years. At first, to Detective Superintendent Roy Grace and his Major Crime Team, these two events seem totally unconnected. But then another young woman in Brighton goes missing and another body from the past surfaces. At the same time a strange man visits an eminent London psychiatrist, claiming to have a piece of information on the missing woman, Logan, that turns out, at first, to be wrong-or so it seems. It is only later Roy Grace makes the chilling realization that this one thing is the key to both the past and the present-and now, beyond any doubt, he knows that Brighton has its first ever serial killer"--
Keywords: Grace, Roy (Fictitious character) -- Fiction; Police -- England -- Brighton -- Fiction; Women -- Crimes against -- Fiction; Serial murder investigation -- Fiction; FICTION / Mystery & Detective / Police Procedural; Mystery fiction; Suspense fiction